New species and new records of Tetranychidae (Acarina, Prostigmata) from Thailand - Naing, Htar Htar; Chandrapatya, Angsumarn; Navajas, Maria; Auger, Philippe (Zootaxa, 2014)
Sampling efforts conducted in several provinces from Thailand disclosed three new species of tetranychid mites. Two of them belong to the genus Tetranychus, namely Tetranychus occultaspina sp. nov. and Tetranychus truncatissimus sp. nov. and the third species belongs to the genus Schizotetranychus, Schizotetranychus krungthepensis sp. nov. They were collected on Ipomoea aquatica, Bambusa multiplex and Saccharum officinarum, respectively. New records and new hosts are also mentioned.